PELATIHAN MEMBUAT ANIMASI MEDIA PEMBELAJARAN BERBASIS POWERPOINT BAGI PARA GURU SEKOLAH DASAR DI DESA SADAHAYU, MAJENANG, JAWA TENGAH - Angkarini, Tri; Mardiyati, Sri; Tanamal, Nini Adelina (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
The training "Creating PowerPoint-Based Learning Media Animations for Elementary School Teachers in Sadahayu Village, Majenang, Central Java" aims to improve teachers' abilities in using PowerPoint animations to create more interesting and effective learning materials. The training involves a series of interactive workshops, practical sessions and demonstrations designed to hone teachers' design and technical skills. Implementation methods include group exercises and performance evaluations to ensure effective knowledge transfer and practical application in the classroom setting. The results of this training showed a significant increase in the technical abilities of teachers in creating animations, as well as an increase in student engagement and interest during the learning process. However, several challenges such as limited technological infrastructure and the need for more training time are problems that need to be addressed to maximize training results. Recommendations for improvement include providing ongoing support and more resources for teachers, as well as developing infrastructure in the schools concerned. The conclusion of this training emphasizes the importance of technology in education and the need to adapt the curriculum to include innovative and interactive teaching methods in the digital era.